Propriedades térmicas e químicas de P3HB modificado por plasma indutivo - Silva, Samuel Victorino Oliveira da (2017)
In this work, the characterization of the plasma treatment effects on the chemical and thermal properties of poly-3-hydroxybutyrate (P3HB), a biodegradable polyester, has been done using FTIR, TGA, XRD and DSC. Two gases were used to provide different plasma treatments: atmospheric air and glacial acetic acid. Samples treated by acetic acid plasma presented notable increase on the degradation temperature as well as reduction of the melting temperature, enough to positively affect the processability of the polymer. The atmospheric air plasma treatment decreased the degree of crystallinity of the polymer while maintaining its thermal performance. Evidences point toward the possibility of the establishment of a paracrystalline form in the plasma-treated samples.